Application of 5S Management in Improving the Quality of Furniture Production in Meubel Karya Agung of Ponorogo Regency - Ilmiah Sholikhah Oktafiani; Subiyantoro Subiyantoro (LP2M STIT Palapa Nusantara, 2022)
5S (Sort, Set in order, Shine, Standardize, dan Self Discipline) is a work culture that must be applied in all workplaces both in the formal and informal sectors. The implementation of 5S aims to make workers feel comfortable and safe while working. In addition, the application of 5S can make work more effective and efficient because it can eliminate wasted time due to more time to search for goods, work areas that look full due to excess equipment and un needed goods or dirty environments. Furniture Works In Semanding District, Kauman, Ponorogo is one of the informal sectors that have not implemented 5R. This is seen from the condition of the work area full of unnecessary equipment and goods, messy, and dirty. Therefore, researchers conducted research analysis of the application of 5S in Furniture Works. Purpose: The purpose of the research to know the application of the principle of 5S in Furniture Works. Method: This research uses qualitative design. The research was conducted with direct observation and using the 5S checklist. Research Results: The results showed that the application of 5S in Furniture Works is still not good. This is evident from the achievement of the 5S as a whole which is below 50%. Conclusion: The results of the study concluded that the implementation of 5S in Furniture Works is still lacking so it is necessary to conduct training on 5S and internal audits periodically.